Deterministic assembly of chromosome ensembles in a programmable membrane trap array. (20th July 2021) - Babahosseini, Hesam; Wangsa, Darawalee; Pabba, Mani; Ried, Thomas; Misteli, Tom; DeVoe, Don L
Abstract: Selective spatial isolation and manipulation of single chromosomes and the controlled formation of defined chromosome ensembles in a droplet-based microfluidic system is presented. The multifunctional microfluidic technology employs elastomer valves and membrane displacement traps to support deterministic manipulation of individual droplets. Picoliter droplets are formed in the 2D array of microscale traps by self-discretization of a nanoliter sample plug, with membranes positioned over each trap allowing controllable metering or full release of selected droplets. By combining discretization, optical interrogation, and selective droplet release for sequential delivery to a downstream merging zone, the system enables efficient manipulation of multiple chromosomes into a defined ensemble with single macromolecule resolution. Key design and operational parameters are explored, and co-compartmentalization of three chromosome pairs is demonstrated as a first step toward formation of precisely defined chromosome ensembles for applications in genetic engineering and synthetic biology.